Płeć kulturowa w rozproszonych systemach poznawczych – możliwości konceptualizacji - Witold WACHOWSKI (Argument, 2015)
There is a mismatch between social and biological approaches in the studies on sex and gender. Neurofeminist researchers critically examine gendered impacts of research in neuroscience and cognitive science, as well as develop more adequate and gender‑appropriate neuroscientific studies. However, they still seem to be focused on the brain and its relationship with the environment. Moreover, there are a little ‘science‑phobic’ feminist approaches based on actor‑network theory, and social science and technology studies. In this context, I would like to suggest another account of gender. My account is not centered on individual selves, minds or brains, but it is based on concept of distributed cognitive system and cultural ecosystem devel‑ oped in the cognitive science. The potential integrational role of the approach seems worthy of attention. On the one hand, there are no contradictions between more important assumptions of distributed cognition theory and social studies. On the other hand, it is not necessarily limited to human beings and their minds. I pay particular attention to distinction between the distributed cognition theory and the extended mind theory. Ones of the most important elements of the ‘gender‑sensitive’ distributed system are artifacts and their affordances, most of all — cultural and canonical ones. In this light, the gender relations seem not only distributed, but also able to be designed.